O circuito financeiro-imobiliário em cidades médias brasileiras: novos condicionamentos na produção do espaço urbano - Ferreira, João Vitor de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
This work aims to analyze the processes and dynamics produced by Real Estate Receivables Certificates (CRIs) in medium-sized cities, seeking to understand their general characteristics and the understanding of their processes of intra-urban spatialization, using as the main source the primary data of emissions produced by Caixa Econômica Federal (CEF) between 2002 and 2016. The analysis seeks to value the articulation of scales present in the real estate financialization processes and understands CRIs as an instrument of the financial system, seeking to analyze them against the global scales of the valuation of the capital, but also through the characteristics of the markets and real estate dynamics of each city. In addition, we seek to understand the mechanisms and agents involved in issuing a CRI and how Brazilian legislation conditions and makes such a particular instrument viable, producing a securitization model different from what was previously pointed out by national and international bibliography. This difference is expressed both in the values of the securitized properties, as in their typologies, which become mostly residential and in the agents involved in the securitization. We also present some of the hypotheses developed during the research, some important questions to think about an agenda of geographic researches about securitization and the results obtained throughout the investigation as the highlight that state agencies assume in the Brazilian securitization model and how this process it spreads through low-value properties.

O trabalho tem como objetivo a análise dos processos e dinâmicas produzidos pelos Certificados de Recebíveis Imobiliários (CRIs) em cidades médias, buscando compreender suas características gerais e o entendimento dos seus processos de espacialização intraurbana, utilizando como fonte principal os dados primários das emissões produzidas pela Caixa Econômica Federal (CEF) entre os anos de 2002 e 2016. A análise procura valorizar a articulação de escalas presentes nos processos de financeirização do imobiliário e compreende os CRIs como instrumento do sistema financeiro, buscando analisá-los frente às escalas globais da valorização do capital, mas também, por meio das características dos mercados e dinâmicas imobiliárias de cada cidade. Além disso, procuramos entender os mecanismos e agentes envolvidos na emissão de um CRI e como a legislação brasileira condiciona e viabiliza um instrumento tão particular, produzindo um modelo de securitização diferente do que até então era apontado pela bibliografia nacional e internacional. Tal diferença é expressa tanto nos valores dos imóveis securitizados, quanto nas suas tipologias, que passam a ser majoritariamente residenciais e nos agentes envolvidos na securitização. Apresentamos ainda algumas das hipóteses desenvolvidas no decorrer da pesquisa, alguns questionamentos importantes para se pensar uma agenda de pesquisas geográficas acerca da securitização e os resultados obtidos ao longo da investigação como o destaque que os órgãos estatais assumem no modelo de securitização brasileira e como esse processo se dissemina pelos imóveis de baixo valor.
The financial-real estate circuit in brazilian medium-sized cities: new constraints on urban space production
Keywords: Real estate market; Financialization; Real estate securitization; Medium cities; Mercado imobiliário; Financeirização; Securitização imobiliária; Cidades médias